Analysis of Stock Investment Decisions on Investors in Surabaya - Sinta Dewi; Tri Kartika Pertiwi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study is to analyze stock investment decisions in investors in Surabaya. This research is quantitative research. The Analysis technique used is the Partial Least Square (PLS) method using primary data. It involved 95 respondents who invested in stocks for more than a year as research objects. The results of the analysis show investors with a good understanding of financial literacy will make the right investment decisions and investors with a high level of financial literacy will be better aware and able to minimize the risks that will be faced but when investors want a high rate of return then investors can tolerate risk in order to get a profit in the future. The absence of a direct relationship between overconfidence to investment decisions can be incarnate in the world of stocks, the most respondents are respondents whose investment experience is 1 year to 3 years, it can be said as a beginner player in stock investing. beginners players are not reliable in making decisions. The most respondents were respondents aged 30-39 years. This age includes a mature age. Respondents with a mature age will be more careful, they do not make an unsecured excess confidence as a reference in acting in investment activities, although an attitude of excessive confidence can help respondents to be able to tolerate risks arising from activities.